Emergencies after endoscopic procedures - Rolanda, C (2013)
Endoscopy adverse events (AEs), or complications, are a rising concern on the quality of endoscopic care, given the technical advances and the crescent complexity of therapeutic procedures, over the entire gastrointestinal and bilio-pancreatic tract. In a small percentage, not established, there can be real emergency conditions, as perforation, severe bleeding, embolization or infection. Distinct variables interfere in its occurrence, although, the awareness of the operator for their potential, early recognition, and local organized facilities for immediate handling, makes all the difference in the subsequent outcome. This review outlines general AEs' frequencies, important predisposing factors and putative prophylactic measures for specific procedures (from conventional endoscopy to endoscopic cholangio-pancreatography and ultrasonography), with comprehensive approaches to the management of emergent bleeding and perforation.